COUMARINS: A UNIQUE SCAFFOLD WITH VERSATILE BIOLOGICAL BEHAVIOR - GUPTA, MANDEEP KUMAR; KUMAR, SUSHIL; CHAUDHARY, SACHIN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Benzopyrones are the club of compounds that can be coumarins or flavonoids. The hydroxyl derivatives of coumarins such as 4-hydroxycoumarins and 7-hydroxycoumarins have extensive biological activities which have employed for the synthesis of miscellaneous coumarin derivatives. These derivatives have exhibited impressive pharmacological and physiological activities such as anticoagulant, antibacterial, antiviral, antitumor, bactericidal, fungicidal, anti-inflammatory agents, and anti-HIV activity. This review comprised pharmacokinetic studies, including absorption, distribution, and metabolism of coumarin analogs along with toxicological studies. The studies of coumarins and their derivatives exhibiting immense pharmacological activity are also summarized in the current study.